Contributions of stress corrosion and cyclic fatigue to subcritical crack growth in a dental glass-ceramic - Joshi, Gaurav V. (Dent Mater, 2014)
OBJECTIVE: The objective of this study was to test the following hypotheses: 1. Both cyclic degradation and stress-corrosion mechanisms result in subcritical crack growth (SCG) in a fluorapatite glass-ceramic (IPS e.max ZirPress, Ivoclar-Vivadent). 2. There is an interactive effect of stress corrosion and cyclic fatigue to accelerate subcritical crack growth. METHODS: Rectangular beam specimens were fabricated using the lost-wax process. Two groups of specimens (N=30/group) with polished (15 µm) or air-abraded surface were tested under rapid monotonic loading. Additional polished specimens were subjected to cyclic loading at two frequencies, 2 Hz (N=44) and 10 Hz (N=36), and at various stress amplitudes. All tests were performed using a fully articulated four-point flexure fixture in deionized water at 37°C. The SCG parameters were determined using the ratio of inert strength Weibull modulus to lifetime Weibull modulus. A general log-linear model was fit to the fatigue lifetime data including time to failure, frequency, peak stress, and the product of frequency and logarithm of stress in ALTA PRO software. RESULTS: SCG parameters determined were n=21.7 and A=4.99×10−5 for 2 Hz, and n=19.1 and A=7.39×10−6 for 10 Hz. After fitting the general log-linear model to cyclic fatigue data, the coefficients of the frequency term (α1), the stress term (α2), and the interaction term (α3) had estimates and 95% confidence intervals of α1= −3.16 (−15.1, 6.30), α2= −21.2 (−34.9, −9.73), and α3= 0.820 (−1.59, 4.02). Only α2 was significantly different from zero.